KAJIAN YURIDIS TENTANG ZAAKWAARNEMING DAN PENERAPAN HUKUMNYA DALAM PUTUSAN NOMOR 1574K/Pdt/2011 MENURUT KUHPERDATA - Dopo, Novita A L; Damat, Petornius; Bire, Chatryen M Dju (Petitum Law Journal, 2025)
Zaakwarneming is a voluntary agreement without any order to that effect. In decision Number 1574 K/Pdt/2011 there is an oral agreement between the Bekasi city government and Pt. Hilma Genractor which causes zaakwarneming. The problem formulation of this research is: (1) Is the spirit of zaakwaarneming legal according to the Civil Code? (2) Is verbal agreement proposed the defendant/applicant for cassation in the case of decision Number 1574 K/Pdt/2011 is categorized as a zaakwaarneming legal act? (3) How is the zaakwarneming law applied in decision Number 1574 K/Pdt/2011? This research uses a normative research method, namely research that examines the literature on primary, secondary and tertiary legal materials related to zaakwarneming. The results of the researchs how (1) Legal Spirit forgets the value of being a support in making laws. Therefore, the legal spirit of zaakwarneming according to the Civil Code is the legal principle of kaptuhan and the legal principle of freedom of contract (2) The verbal agreement in decisioncase Number 1574 K/Pdt/2011 cannot be categorized as a legal act of zaakwarneming, because the land clearing work was carried out by the plaintiff is not in the work contract so it does not fulfill the requirements of an agreement in Article 1320 of the Civil Code (3) considerations for the public interest and verbal agreement made by the defendant, thus the plaintiff carried out work outside the contract in good faith.